The Legal Sure of Marriage Itsbat Towards The Status of Marriage (Study of The Decision of The Takalar Religious Court) - Hudalinnas h; Syamsuddin Pasamai; Hamza Baharuddin (Gerechtiheid Law Journal, 2020)
The marriage ceremony is one of the government's efforts to provide services to people who do not yet have a marriage certificate to register their marriage again, so that they have legal certainty for their marital status. This research was conducted with the aim of knowing the implications that arise after the marriage ceremony by the judges at the Takalar Religious Court and to determine the factors that encourage husband and wife to propose marriage certificate. The method used in this research is the normative juridical method through two approaches, namely the statute approach and the case approach. The reason for using this method is because legal research is a process to find legal rules. The results showed that the implication of marriage status on marital status is related to the principle of legal certainty, namely by the existence of marriage, which was previously carried out, namely marriages that were not recorded by the Registrar of Marriages, making the marriage have legal certainty, meaning that it is in accordance with the legal objective, namely to regulate order. society in a peaceful and just manner and the marriage becomes legal. Itsbat nikah provides a foundation of certainty on the validity of the status of the child born. Meanwhile, the legal certainty of the status of marriage regarding the status of marital assets becomes clear about the ownership of joint assets.